ANALISIS MODEL SISTEM ANTRIAN PADA PELAYANAN RESTORAN KOBER MIE SETAN JEMBER - Bambang Herry Purnomo; Yuli Wibowo; Geby Yogita Aditya (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Kober Mie Setan is the restaurant that so famous in various circles from students to the general public range because it has its characteristics that can make people feel curious and want to visit to try the product. Kober Mie Setan Jember Restaurant getting more crowded thus giving an impact on the length of the existing queue. To overcome the problems that occur in a queue, then there is a need for analysis to identify and measure a queue, and optimization is needed to a queue that is less than optimal in service. The purpose of this research was to determine and analyze the queuing system model applied in Kober Mie Setan Jember Restaurant and formulate recommendations for queuing system improvements that can reduce queue length and minimize queuing costs. The method used is a calculation with queuing theory and simulation using ARENA. The data used are the arrival time data, server service time, and queue costs. The results show that the queuing system model in Kober Mie Setan Jember Restaurant in the current condition is Single Channel Multi-Phase. The number of facilities at the cashier is 1 facility with 2 employees and the kitchen facility is 1 facility with 6 employees. Queue discipline used is FIFO (First In First Out). The level of the arrival of customers with Poisson distribution and customer service time with Exponential distribution. Based on the results of several improvement scenarios, the most optimal scenario is by adding 1 cashier facility and 1 kitchen employee. Recommended queue models suitable for cashier facilities are (M/M /2); (FIFO/∞/∞) and kitchen facilities are (M/M/1); (FIFO /∞/∞), with a Multi Channel-Multi Phase queuing system. Costs incurred for the addition of facilities based on selected scenarios are Rp249,833,- per hour which is the most minimal cost.